2008
DOI: 10.1212/01.wnl.0000336969.98241.17
|View full text |Cite
|
Sign up to set email alerts
|

Nerve fiber impairment of anterior thalamocortical circuitry in juvenile myoclonic epilepsy

Abstract: The results support the hypothesis that juvenile myoclonic epilepsy is associated with abnormalities of the thalamocortical network that can be detected by diffusion tensor MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
112
2
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 33 publications
(29 reference statements)
13
112
2
2
Order By: Relevance
“…DTI studies have been reported in patients with epilepsy associated with frontal lobe dysfunction and they have found similar findings. DTI studies in juvenile myoclonic epilepsy, an idiopathic generalized epilepsy with frontal lobe dysfunctions, showed abnormal WM in supplementary motor area, bilateral superior and anterior corona radiata, genu and body of corpus callosum, and multiple superior and middle frontal WM tracts, and thalamofrontal connections (Deppe et al, 2008;Kim et al, 2012b;O'Muircheartaigh et al, 2011). The WM in the frontal lobe has also been examined using DTI in 12 children with drug resistant partial epilepsy (Holt et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…DTI studies have been reported in patients with epilepsy associated with frontal lobe dysfunction and they have found similar findings. DTI studies in juvenile myoclonic epilepsy, an idiopathic generalized epilepsy with frontal lobe dysfunctions, showed abnormal WM in supplementary motor area, bilateral superior and anterior corona radiata, genu and body of corpus callosum, and multiple superior and middle frontal WM tracts, and thalamofrontal connections (Deppe et al, 2008;Kim et al, 2012b;O'Muircheartaigh et al, 2011). The WM in the frontal lobe has also been examined using DTI in 12 children with drug resistant partial epilepsy (Holt et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Since Gloor et al 3 first suggested that an abnormal cortical response to thalamocortical afferents might be responsible for generalized seizures, there is considerable evidence that thalamocortical networks are pathophysiologic in IGE. [4][5][6] Previous imaging studies have shown consistent structural and functional thalamic and cortical abnormalities, particularly in the frontal lobes, 7,8 and thalamofrontal white matter connectivity. 5 The thalamus and frontal lobes have extensive anatomic interconnectivity with bidirectional pathways 9 and both structures are involved in generalized spike wave discharges associated with IGE.…”
mentioning
confidence: 89%
“…[4][5][6] Previous imaging studies have shown consistent structural and functional thalamic and cortical abnormalities, particularly in the frontal lobes, 7,8 and thalamofrontal white matter connectivity. 5 The thalamus and frontal lobes have extensive anatomic interconnectivity with bidirectional pathways 9 and both structures are involved in generalized spike wave discharges associated with IGE. 10 The timing of the onset, manifestation, and development of thalamofrontal abnormalities in IGE is poorly defined.…”
mentioning
confidence: 89%
“…[8] can be constructed for each of the other EC deformations: [12] where the normalized coefficient vectors are given by:ˆ α n = c α n (n = x, y , z), and c is the same constant as in Eq. [7].…”
Section: Ec Field and Distortionsmentioning
confidence: 99%
“…, 13), where the i-th element of the EC vector contains the EC parameters obtained from the correction of the i-th DW image (see also Eq. [8]). To minimize interindividual variations, the EC vectors were averaged over 13 subjects (N sub = 13).…”
Section: Group-averaged Ec Parametersmentioning
confidence: 99%